2021
DOI: 10.5755/j01.ee.32.5.26032
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Perception of Human Capital, Innovations, and Performance: Evidence from Banking Industry

Abstract: This paper aims to examine the relationship between the managerial perception of human capital, innovations, and bank performance. We specifically sought to examine the influence of human capital on bank performance, by introducing the factors of innovation speed and quality. The study was taken in the Serbian banking industry, with the focus on the perception and the viewpoint of CEOs and general managers of different departments. We used a two-phase survey to design the questionnaire and the correlation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…This is the most important component of IC and outperforms other components (Ousama et al, 2019;Yao et al, 2019). In addition, human capital can be critical to the bank's performance and innovation speed (Milosevic et al, 2021). Nonetheless, certain studies confirmed that HCE can negatively affect banks' performance (Rehman et al, 2021).…”
Section: 2020mentioning
confidence: 98%
See 2 more Smart Citations
“…This is the most important component of IC and outperforms other components (Ousama et al, 2019;Yao et al, 2019). In addition, human capital can be critical to the bank's performance and innovation speed (Milosevic et al, 2021). Nonetheless, certain studies confirmed that HCE can negatively affect banks' performance (Rehman et al, 2021).…”
Section: 2020mentioning
confidence: 98%
“…). There is also a substantial body of research on the link between human capital and bank success (Milosevic et al, 2021).…”
Section: 2020mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicator demonstrates the speed at which new and innovative concepts emerge inside an organization (Adusei et al, 2023). This can result in a more agile and adaptive innovation channel (Dong et al, 2019;Milošević et al, 2021).…”
Section: New Idea Generation Speedmentioning
confidence: 99%
“…In addition, digital innovations neutralize the risks of information and cybercrime in the financial sector (Hassan & Lee, 2021). At the current stage, the speed of implementation of banking innovations is a key factor in ensuring its effectiveness (Milosevic et al, 2021;Stark, 2021;Popova, 2021;Ibrahimov et al, 2021). In the banking sector, the intensity of digital transformations depends on the quality of strategic planning (Tran et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%